Globalization of Western Culture and Its Impact on Changes in Muslim Fashion Styles - Fathimah Azzahra Safrizal (Al-Abqori: Journal of Islamic Thought Studies, 2025)
Rapidly developing technology allows one country to peek at and even imitate the culture of another country, one nation adopts another nation's culture. As is happening among Muslim women today where the style of dress should have been contaminated with foreign culture. Focused on the globalization of western culture, this paper aims to discuss the impact that has occurred on the success of the Western worldwide culture with the intention of destroying the faith and sharia of Muslims, especially the Muslimah fashion style. This research was conducted using the literature study method by collecting existing data to strengthen arguments and ideas. Research results include; 1) the globalization of western culture has shifted the function of clothing according to sharia to become a trend and fashion. 2) less shame on women, 3) minimal western-style clothing is one of the triggers for sexual harassment. Quoting one of the great Islamic scholars, Yusuf al-Qardhawi advised Muslim women to return to the Islamic millah, the style of dress that the Shari'a has prescribed so that life can be calm and relaxed. Interpreting taqwa clothing is not only an abstract meaning but is manifested in a physical form that is reflected in the actual Muslimah fashion style.